The Use of Alternative Benchmarks in Anti-Subsidy Law A Study on the WTO, the EU and China - Müller, Sophia (EYIEL Monographs - Studies in European and International Economic Law,, 2018)
In the debate over the treatment of China in trade remedy investigations, this book focuses exclusively on anti-subsidy law. As such, it brings a long neglected and often underestimated area of international trade law to the fore. Exploring the delicate relations between the WTO, the EU and China, it focuses on the current legal framework for the use of alternative benchmarks in anti-subsidy law and analyses the consequences that arise from its practical application in investigations against China. Scrutinizing recent developments in WTO anti-subsidy law, in particular the adoption of country-specific rules in accession protocols, the book reveals the shortcomings of the current approach and argues for fundamental reforms. Accordingly, the book provides academics and practitioners alike with vital insights into the legal evolution and practical application of alternative benchmark methodologies in the context of WTO and EU anti-subsidy law, while also putting forward a critical analysis of the status quo.